2021
DOI: 10.1016/j.cmi.2021.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response induced by the BNT162b2 mRNA COVID-19 vaccine in a cohort of health-care workers, with or without prior SARS-CoV-2 infection: a prospective study

Abstract: Objectives We assessed the antibody response to BNT162b2 mRNA COVID-19 vaccine in a cohort of health care workers (HCW), comparing subjects with previous SARS-CoV-2 infection and naïve subjects. Methods HCW were tested at T0 (day of first dose), T1 (day of second dose), and T2 (2-3 weeks after) for IgG anti nucleocapside protein, IgM anti spike protein and IgG anti receptor binding domain (IgG-RBD-S). The antibody response was compared between 4 main groups: A) Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 19 publications
10
40
2
Order By: Relevance
“…This reassuring finding stands in contrast to a recent publication from Italy that describes lower antibody levels in fully vaccinated COVID-19-naïve individuals [ 26 ]. Other groups showed that a second booster dose given after the first booster vaccination to patients with previous COVID-19 did not increase antibody levels further [ 25 , 27 ].…”
Section: Discussioncontrasting
confidence: 89%
“…This reassuring finding stands in contrast to a recent publication from Italy that describes lower antibody levels in fully vaccinated COVID-19-naïve individuals [ 26 ]. Other groups showed that a second booster dose given after the first booster vaccination to patients with previous COVID-19 did not increase antibody levels further [ 25 , 27 ].…”
Section: Discussioncontrasting
confidence: 89%
“…More interestingly, we found that vaccine-induced antibody level was significantly high after 2 weeks from the single dose of SARS-CoV-2 mRNA vaccine in HCWs with preexisting immunity. Several data showed that one dose of the BNT162b2 vaccine (as well as other COVID-19 vaccines) maximizes the cellular and humoral immune response to S1 spike protein in subjects with previous SARS-CoV-2 infection and our results corroborate the hypothesis that previous SARS-CoV-2 infection may be considered an analogous to immune priming [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 85%
“…Antibody titers were significantly higher in women and in younger participants even more than three months after the second dose of the vaccine. Several studies have indicated that sex and age are associated with antibody responses [ [11] , [12] , [13] ], and the findings of this study are consistent with these reports. Kageyama et al reported that the use of medications for allergies had a correlation with lower antibody titers [ 13 ], although the results from this study showed no association.…”
Section: Textsupporting
confidence: 92%